Comparison of two Jatropha species (Euphorbiaceae) used popularly to treat snakebites in Northeastern Brazil: Chemical profile, inhibitory activity against Bothrops erythromelas venom and antibacterial activity. (1st March 2018) - Félix-Silva, Juliana; Gomes, Jacyra A.S.; Fernandes, Júlia M.; Moura, Angela K.C.; Menezes, Yamara A.S.; Santos, Elizabeth C.G.; Tambourgi, Denise V.; Silva-Junior, Arnóbio A.; Zucolotto, Silvana M.; Fernandes-Pedrosa, Matheus F.
Abstract: Ethnopharmacological relevance: Jatropha species (Euphorbiaceae) are largely used in traditional medicine to treat different pathologies in Africa, Asia and Latin America. In Northeastern Brazilian folk medicine, several Jatropha species, such as Jatropha gossypiifolia L. and Jatropha mollissima (Pohl) Baill., are indistinctly used to treat snakebites. Aim of the study: To compare two of the Brazilian most used Jatropha species for snakebites ( J. gossypiifolia and J. mollissima ), in relation to their ability to inhibit local edematogenic activity of Bothrops erythromelas snake venom in mice, their in vitro antibacterial activity and phytochemical profile. Material and methods: Aqueous leaf extracts of J. gossypiifolia (AEJg) and J. mollissima (AEJm) were prepared by decoction. AEJg and AEJm were compared chemically, by thin layer chromatography (TLC) and high-performance liquid chromatography with diode array detection (HPLC-DAD) analysis. They were also pharmacologically compared, using the mouse model of paw edema induced by Bothrops erythromelas snake venom (BeV), and in vitro by broth microdilution and agar dilution antimicrobial tests. Results: Flavonoids were detected as the major compounds in both extracts. However, AEJg and AEJm showed quantitatively different chemical profiles by HPLC-DAD. AEJg presented fewer peaks of flavonoids than AEJm, however, when the intensity of peaks were analyzed, these compounds were at high concentration in AEJg, even using the same concentration of both extracts. Differences were also observed in the biological activity of the two extracts. While no difference was observed when the extracts were administered by oral route ( P > 0.05), by the intraperitoneal route AEJg presented anti-edematogenic activity significantly ( P < 0.001) higher than AEJm. In antimicrobial assays, only AEJg presented antibacterial activity against Staphylococcus epidermidis, Staphylococcus aureus and Bacillus cereus . Conclusions: Although used indistinctly by folk medicine, our results suggested that AEJg is more active than AEJm in relation to its antiedematogenic and antibacterial activities. Significant differences were observed in their phytochemical profiles, especially a higher content of C -glycosylated flavonoids in the most active species, which could justify the different biological effects observed. These findings strengthen the potentiality of J. gossypiifolia species for use as complementary treatment for local effects induced by Bothrops venoms and could be helpful for distinction of the species and control quality assessment of future herbal medicines based on Jatropha plants. Graphical abstract: